Risk based pricing for unsecured lending - Thoka, Boitumelo (My University, 2015)
Risk based pricing has been a topic of discussion since the 2008 financial crisis as a result of the on-selling of packaged sub-prime assets. This paper will highlight the importance of correctly assessing risk within the framework of consumer credit provision. We will begin with a brief overview of the South African unsecured lending market, look into the definition of risk based pricing and the impact it has had in the market and conclude the paper by using a model by Robert Phillips to calculate the interest rate to be offered to a customer.
Thesis submitted in fulfillment of the requirements for the degree of Master of Management in Finance & Investment In the Faculty of Commerce and Law Management Wits Business School at the University of the Witwatersrand, 2015
Keywords: Credit scoring systems--South Africa; Bank loans--South Africa; Consumer credit--South Africa; Risk management--South Africa